Tax Relief and Tax Preferences in Income Tax in Poland - Ciuman, Krystyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The article presents tax relief and tax preferences in income taxes (PIT and CIT) in Poland in the years 2010–2015. Tax relief is understood as the possibility of reducing the earned income or calculated tax by certain amounts (mainly under the Act on tax). Income relief reduced the amount of the tax base, and thus indirectly affected the amount of tax. On the other hand, tax relief led to a tax reduction by the amount of the relief. In turn, tax preferences were interpreted as derogations from the country’s tax standard.Both tax relief and tax preferences are an important instrument of fiscal policy that is conducive to implementing tax regulatory and stimulating functions. However, they cause a decrease in budget tax revenues, if to varying degrees. The article characterises the size, structure and tendency of the development of tax relief and preferences, as well as the extent to which they have contributed to the reduction of budget revenue from personal income tax and corporate income tax.